Dinamika Pesan Kampanye Politik Kandidat Lokal melalui Instagram: Dari Citra hingga Partisipasi - Dian Permanasari; Farid Aji Prakosa (Universitas Muhammadiyah Klaten, 2026)
Social media has become an important arena for political campaigning because it enables candidates to present themselves, frame issues, and invite public involvement through visual and interactive communication. However, many studies still emphasize visual appearance or engagement metrics, while the temporal movement of campaign messages receives less attention. This study analyzes the dynamics of local candidate campaign messages on Instagram, particularly the shift from image building to participation appeals. A descriptive qualitative approach with qualitative content analysis was employed. The data consisted of 45 Instagram feed posts published by a candidate for the Regional Representative Council from the Special Region of Yogyakarta during an intensive one-month campaign period before voting day. Each post was coded according to campaign phase and message function, covering image building, social proximity, electoral education, and participation appeals. The findings show a gradual pattern. Early posts emphasized image building through gender, local culture, micro-enterprise, environmental, and innovation issues. The middle phase strengthened social proximity through market visits, community encounters, local language, and aspiration channels. The final phase was dominated by participation appeals through electoral information, campaign events, slogans, quizzes, and voting encouragement. The study concludes that Instagram functions not only as a visual campaign medium, but also as a space for organizing the rhythm of local political communication from image building toward audience participation.